Real estate cadastral data collection problems, imaging and works intensity in Lithuania - Gaudėšius, Rimvydas (Geodesy and Cartography, 2014)
Immovable properties mainly include land and objects related to it and that are not possible to be moved from one place to another without changing their purpose and decreasing their value. Legal ownership to this property has always been and will always be important for an individual. Registration of the real estate (thereinafter – RE) and information about drawn up ownership is the foundation for creation of any other systems. Geographic information system (thereinafter – GIS) being used wider in all over the world, data bases containing information about registered property are being created. RE registration systems are related to economically and politically advanced societies and whereas states are differently advanced on a social environmental level, this process is also unevenly developed in different countries; the importance, accuracy and presentation of registered data to concerned society are valued differently, too. The scientific article analyses real estate cadastral data bases existent in Lithuania that are created by different institutions, prevalent features of data evaluation and related problems. Characteristics of cadastral data collection in other states are also reviewed. Posed the problem of inaccuracy of cadastral data collected, who influences a dispute and frauds. Moreover, the article draws attention to the necessity to improve the process of works performed in Lithuania in order to simplify data determination and increase its accuracy. The article also shows the intensity of the work performed in the administrative areas and after calculations are made, further course of works will be forecasted.